An analysis of gas-induced explosions in vented enclosures in lithium-ion batteries. (July 2022) - Ogunfuye, Samuel; Sezer, Hayri; Said, Ahmed O.; Simeoni, Albert; Akkerman, V'yacheslav
Abstract: Lithium-ion batteries (LIBs) have found wide usage and tremendous technological advancements in recent years, due to their numerous advantages, but the safe utilization of LIBs has been a major concern, which research, industry, and government agencies seek to address. During a LIB failure, a fire or explosion hazard may occur, depending on the failure mechanism, and safety vents can be designed to mitigate the explosion induced by gases released from LIBs in an enclosure. In the present study, explosion hazards of LIBs are analyzed, and a numerical model for gas explosion venting is developed and validated using experiments on hydrogen and methane explosions. Furthermore, the explosion characteristics of various hazardous gas mixtures emitted from LIBs at various equivalence ratios predicted by the model are compared to the NFPA 68 standards. The lithium‑cobalt oxide (LCO), lithium‑iron phosphate (LFP), lithium‑nickel‑cobalt‑aluminum oxide (NCA) and lithium‑nickel‑manganese‑cobalt oxide (NMC) batteries are used to determine the impact of battery chemistry, vent size, as well as the state of charge (SoC) of the batteries on the explosion characteristics. The impact of the equivalence ratio of the vented gas is also investigated as well as that of accounting for CO2 among the vented gas on the predicted peak pressure. In addition, the sensitivity of the explosion severity to variability in vented gas composition is also scrutinized. Highlights: Numerical model was developed to characterize explosion hazards resulting from explosion of lithium-ion batteries. Explosion hazards of lithium batteries were analyzed during failure. The impact of battery chemistry, vent size, and SoC of lithium-ion batteries on explosion characteristics were considered. Impact of equivalence ratio and vented gas composition of lithium-ion batteries on the predicted pressure was studied. Sensitivity of the explosion severity to variability in vented gas composition was scrutinized.